Modified PLGA nanofibers as a nerve regenerator with Schwann cells - Zolfaghari, Davood; Tebyanian, Hamid; Soufdoost, Reza Sayyad; Emamgholi, Askar; Barkhordari, Aref; Herfedoost, Gholam Reza; Kaka, Gholam Reza; Rashidiani, Jamal (Cellular and Molecular Biology, 2018)
Polylactide-co-glycolide acid (PLGA) is known as a biodegradable and biocompatible polymer. This polymer has been highly used in tissue engineering. In this study, the biological behavior of Schwann cells (Rat) was investigated in co-culture with L lysine/gelatine coated PLGA nano-fiber. In this study, PLGA was dissolved in a hexafluoro propanol based solvent and nanofiber prepared by an electronic method. They were coated with gelatin and poly-L-lysine individually. These polymer properties were investigated by Scanning Electron Microscopy (SEM) analysis and contact angle measurement. After extraction of rat Schwann cells, the cells were cultured in three groups of nano-fiber; nano-fiber PLGA, nano-fiber gelatine coated PLGA and nano-fiber poly-L-lysine coated PLGA. Cell death and Cell proliferation were evaluated by Acridine orange staining (living cell with a green nucleus and dead cell with an orange nucleus) and morphology was investigated by SEM in 2, 4 and 6 days. The diameter of electronic nanofiber PLGA was between 270 to 700 nm. Average contact angles of PLGA, PLGA coated with gelatine, coated with poly-L-lysine and PLGA were 40.12, 64.58 and 107.66degrees, respectively. The findings showed a significant reduction of cell proliferation in PLGA nanofiber ( it was important than PLGA without nano-fiber (P <0.05)). But, this amount was increased in nanofiber which coated with poly-L-lysine and gelatine. PLGA nanofiber-poly-L-lysine was more biocompatible than PLGA nanofiber-gelatine and this comparison was done with rat Schwann cells.